Minimal change in achievement in high-stakes mathematics examinations in low socio-economic status environments in post-apartheid South Africa - Benita P. Nel; Cyril Julie; Faaiz Gierdien; Marius Simons; Bruce May (Interdisciplinary Journal of Sociality Studies, 2024)
Since various curriculum versions have been implemented in the post-apartheid era, achievement results in high-stakes mathematics examinations are still structured along socio-economic status lines. Continuing professional development (CPD) for mathematics teachers is widely viewed as a mechanism to address this issue. This study uses a specific CPD project to explore the question, “Are three decades-long enough to enhance achievement outcomes in high-stakes mathematics examinations for learners from low socio-economic status environments?” Bricolage is employed as the underlying research framework due to the multifaceted nature of CPD. In one of the residential institutes in 2018, a 7-item questionnaire, based on features of effective CPD and containing four ordinal response categories, was administered to 55 participating teachers (30 females and 25 males). To acknowledge the complex nature of CPD, themes were developed and primarily analysed using descriptive statistics. The analysis revealed that, although mathematics teachers respond favourably to practising previously taught material, there are factors that hinder the sustainability of such an approach. It is concluded that 30 years is not a sufficient timespan to expect significant change. It is recommended that drastic measures be taken regarding the continuing professional development of mathematics teachers to address disparities along class and racial lines.